2012
DOI: 10.5194/cp-8-705-2012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing extreme droughts in Spain during 1750–1850 from rogation ceremonies

Abstract: Abstract. Among the different meteorological hazards,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 55 publications
4
39
0
Order By: Relevance
“…Both indices also agreed to identify the major drought occurred in Barcelona between years 1822 and 1825 and the wettest event to years 1971 and 1972. This is in good agreement with Prohom et al (2015) who listed the years 1822, 1823 and 1824 into the top six of the driest years in Barcelona (1787Barcelona ( -2014 during the exceptional dry period occurred in the early 19th century (Domínguez-Castro et al, 2012), while the wettest year of the time series was also 1971. From the similarities found in both the SPI and SPEITh series can be concluded that precipitation is the main driver on drought variability according to drought indices, but reference evapotranspiration (only included in the SPEITh) is playing a substantial role in explaining drought severity especially during the last three decades.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both indices also agreed to identify the major drought occurred in Barcelona between years 1822 and 1825 and the wettest event to years 1971 and 1972. This is in good agreement with Prohom et al (2015) who listed the years 1822, 1823 and 1824 into the top six of the driest years in Barcelona (1787Barcelona ( -2014 during the exceptional dry period occurred in the early 19th century (Domínguez-Castro et al, 2012), while the wettest year of the time series was also 1971. From the similarities found in both the SPI and SPEITh series can be concluded that precipitation is the main driver on drought variability according to drought indices, but reference evapotranspiration (only included in the SPEITh) is playing a substantial role in explaining drought severity especially during the last three decades.…”
Section: Discussionsupporting
confidence: 88%
“…Extremely dry conditions were also found in southern Europe for the period 1808-1835 according to Pauling et al (2006). The main cause of this extremely dry period was the large decrease of precipitation due to the high volcanic activity during the solar Dalton Minimum in the early 19th century (Anet et al, 2014;Domínguez-Castro et al, 2012). Barcelona (1901Barcelona ( -2014 based on the Thornthwaite (Th) and Hargreaves (Hg) …”
Section: Description Of Drought Variability By Using Spi and Speimentioning
confidence: 99%
“…Spain is highly affected by droughts [14,15], and various major drought episodes occurred during the 20th century, some of which affected the country for several years [16,17]. Droughts in Spain have severe economic impacts [18], including affecting the availability of water resources [19], causing forest decline and mortality [20,21], reducing vegetation activity [22], and causing failures in crop yields [23].…”
Section: Introductionmentioning
confidence: 99%
“…Neukom et al ., ; Prieto and García‐Herrera, ), the Arab world (e.g. Bulliet, ; Domínguez‐Castro et al ., , ), Africa (e.g. Gallego et al ., ; Nicholson et al ., ; Nash et al ., ), or Oceania (e.g.…”
Section: Introductionmentioning
confidence: 99%